Inventory Management of Educational Facilities for Enhancing School Management Effectiveness - Abdillah Naufal Abror; Sedya Santosa; Muhammad Azmi Auf; Syariful Huda (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
This study examines the dual curriculum as an integrative model for improving educational quality in response to the growing need for adaptive and holistic learning frameworks. Using a Systematic Literature Review (SLR) guided by PRISMA 2020 procedures, this study synthesizes findings from 43 selected articles retrieved from Scopus, Google Scholar, and the Directory of Open Access Journals (DOAJ), covering diverse educational contexts including Islamic boarding schools, higher education, and vocational education. The analysis conceptualizes the dual curriculum as a multidimensional framework that integrates curriculum design, pedagogical practices, institutional leadership, and policy alignment. The findings indicate that dual curriculum implementation is associated with improvements in academic competence, critical thinking, social literacy, and learners’ readiness to meet evolving societal and workforce demands. These outcomes are influenced by key enabling factors such as leadership commitment, teacher capacity, and institutional support. However, several challenges persist, including increased curricular load, tensions between differing knowledge paradigms, socio-cultural resistance, and limitations in assessment practices. This study contributes to the field of educational management by offering a synthesized conceptual model that positions the dual curriculum as a cross-contextual and adaptive integrative framework. It also highlights the importance of systemic alignment across educational dimensions and underscores the need for more rigorous comparative and empirical research to strengthen the evidence base of dual curriculum implementation.